Recurrent Laryngeal Nerve Injury Secondary to Blunt Trauma; A Rarity - Baithma Jothi Dinesh; Zubaidah Sharif Siti; Lai, Dexter Zen Ran; Firdaus Hayati (2018)
Recurrent laryngeal nerve (RLN) injury is rarely seen following trauma. Trauma can be penetrating or blunt injury. Following the acute event, the most common presentation is hoarseness of voice. Herein we present a case of recurrent laryngeal nerve injury noticed after a blunt trauma. Indirect laryngoscopy helps to identify and diagnose vocal cord palsy while Computed Tomography (CT) scan of neck helps to evaluate the extent of injury as well as to identify the primary cause of the injury. Patient morbidity can be reduced with prompt diagnosis and management.